The Effect of Work Placement and Compensation on Employee Performance through Work Motivation - Masyhudi, Muh Syahid; Hardianti, Hardianti; Kadir, Abd Rahman; Parawansa, Dian A. S. (Faculty of Economics and Business, Hasanuddin University, 2023)
This research aims to analyze Job Placement which has an indirect influence on employee performance through work motivation and to analyze Compensation which has an indirect influence on employee performance through work motivation at the at the First-class SFR Monitoring Hall Office Makassar. This study uses a quantitative approach. The data used is primary data. The sample was 30 respondents. The respondents are permanent employees who work within the First-class SFR Monitoring Hall Office Makassar. Data collection was carried out through surveys using questionnaires distributed to respondents. Data were analyzed using multiple regression analysis and path analysis with the Statistical Package for the Social Sciences (SPSS) version 26. The research results show that work placement and compensation have a direct influence on employee performance through work motivation. at the First-class SFR Monitoring Hall Office Makassar, and there is an indirect influence on employee performance through work motivation at the Makassar Class I SFR Monitoring Office. This shows that when work placement and high compensation are followed by high work motivation, employee performance will increase and vice versa.